PENGARUH BUDAYA ORGANISASI DAN STRES KERJA TERHADAP KINERJA SALES PT INFOMEDIA NUSANTARA DI KOTA DEPOK - Fachri Hayqal (2021)
The Research is a quantitative study that aims to determine and prove the Influence of Organizational of Culture and Work Stres on the Sales Performance of PT Infomedia Nusantara in Depok City. This Research uses a sample of 60 respodents which is the total number of sales of PT Infomedia Nusantara in Depok City. In this research, the analysis technique uses t test (partial), F test (simultaneous), and coefficient of determination test (R2) which is assisted by using SPSS version 26 software. The test result show that (1) organizational culture has a significant effect on sales performance of PT Infomedia Nusantara in Depok City, (2) work stres has a significant effect on the sales performance of PT Infomedia Nusantara in Depok City, (3) organizational culture and work stres simultaneously have a significant effect on sales performance of PT Infomedia Nusantara in Depok City.